State-of-the-art surgery for pancreatic cancer - Nießen, Anna; Hackert, Thilo (Langenbeck's archives of surgery, 2022)
The development of surgical techniques and specialization and specifically complication management in pancreatic surgery have improved surgical outcomes as well as oncological results in pancreatic surgery in recent decades. Historical morbidity and especially mortality rates of up to 80% have decreased to below 5% today. This review summarizes the current state of the art in pancreatic cancer surgery.
Online veröffentlicht: 9. November 2021
Gesehen am 17.08.2023